Tethys ocean withdrawal and continental peneplanation—An example from the Galilee, northwestern Arabia. (October 2019) - Wald, R.; Segev, A.; Ben-Avraham, Z.; Schattner, U.
Graphical abstract: Highlights: Interpreting scarce, isolated, basin-sheltered intra-plate Oligocene sediments. Analysis of three tectono-sedimentary packages portrays the Oligocene truncation. The northward propagation arm of the Afar plume is suggested as an uplift mechanism. Abstract: During the early Oligocene northeast Africa (Ethiopia, Sudan, Egypt) and Arabia (Yemen, Saudi Arabia, Jordan, Sinai and southern Israel) progressively emerged from marine conditions. Their complete subaerial exposure was accompanied by widespread erosion. Its products were transported across northeast Gondwana to the nearby Mediterranean and Mesopotamian basins while leaving behind a Regional Truncation Surface (RTS). The uplift mechanism is debated. Some claim it results from the Oligocene updoming of Afar mantle plume across northeastern Gondwana. Others suggest GondwanaEurasia convergence that reached hard-docking during the Oligocene is the dominant process. Miocene-to-Holocene post-truncation tectonics deformed the leveled RTS (peneplain) relief while erosion continued. As a result, only scarce and widely distributed evidence for erosion remained across Arabia. The current study addresses this debate through the examination of the morphological development of the converging plate on the verge of entering the subduction zone. The study focuses on the mode of erosion across the Galilee basins of northern Israel. Based on the interpretation of 69 multichannel seismic reflection profiles (extending along 800 km), correlated with 68 boreholes and all previous geological mapping, we distinguish between pre-, syn- and post-truncation stratigraphic units. Results show that the RTS subcrop comprises a mosaic of diachronous formations, spanning the Upper Cretaceous and Oligocene. Stratigraphy constrains the overall duration of truncation between Late Eocene and Early Miocene. A new observation into the truncation period shown here enhances the morphological expression of ocean bottom exposure. The maximum thickness of strata removed reaches ˜1300 m during a 7 ± 2 million year time window. A conservative time estimation yields a weathering rate of 0.186 ± 0.058 mm per year, under a subtropical climate suggested for the Oligocene in this region. Preservation of syn-truncation sediments in local fault-bounded depressions attests to a regional NNE trending flexural uplift accompanied by local extensions. Truncation sediments derived from these erosional events accumulated across the western and eastern flanks of the Galilee, under marine conditions. We suggest that this flexure developed along a northward propagating arm of the Afar plume. This case study may serve as an example for the morphological development of a tectonic plate before its entrance into a subduction zone.